PENERAPAN PRINSIP “THE BEST INTEREST OF THE CHILD” PADA KEHIDUPAN ANAK YANG TERPAKSA BEKERJA DI INDONESIA - Evans Angokaming Djehadut; Ni Putu Purwanti (Kertha Negara : Journal Ilmu Hukum, 2013)
The presence of children who are forced to work in Indonesia creates rulesgoverning restrictions on what jobs that can be done and in what jobs the children wereforbidden to work. Related to the principle of